UPAYA PELATIH DALAM MENGATASI KECEMASAN ATLET SENAM SEBELUM PERLOMBAAN PADA PEKAN OLAHRAGA PELAJAR NASIONAL 2009 - Endang Rini Sukamti; Irwan Taufik Hidayat (Jorpres (Jurnal Olahraga Prestasi), 2016)
This research discuss about the instructor's effort to conquer the gymnast's anxiety before POPNAS event 2009. The purpose of this research is to know how high the instructor's effort to conquer the gymnast's anxiety wether influence by intrinsic factor or extrinsic factor before race in POPNAS 2009.This research belongs to descriptive research using survey method. The sample of research population is taken from artistic's gymnast male or female and 44 instructor's sportif rhythmic from whole instructors in POPNAS 2009. The questionnaire is used as the research instrument to collect the data. In analizing the data, researcher using percentage quantitative descriptive technique.The research indicate that the instructor's effort to conquer the gymnast's anxiety on intrinsic factor before POPNAS race 2009 on high category 50,00 %, while the high category of extrinsic factor reach 52.3 %, and the effort of instructor to conquer the gymnast's anxiety before POPNAS on high category 50,00 %. Kata Kunci: Pelatih, Kecemasan, Atlet